Effects of increased alcohol availability during adolescence on the risk of all‐cause and cause‐specific disability pension: a natural experiment. (7th February 2017) - Thern, Emelie; de Munter, Jeroen; Hemmingsson, Tomas; Davey Smith, George; Ramstedt, Mats; Tynelius, Per; Rasmussen, Finn
Abstract: Aim: To test if being exposed to increased alcohol availability during adolescence is associated with an increased risk of receiving disability pension due to all‐cause, alcohol use disorders and mental disorders. Design: Register‐based population‐based study using a natural experiment setting, the alcohol policy change in Sweden (1967–68), with increased access to strong beer in a narrow time window and geographical area. The individuals exposed to the policy change were compared with non‐exposed individuals living in the rest of Sweden, excluding a border area. Setting: Sweden. Participants: A total of 518 810 individuals (70 761 in the intervention group; 448 049 in the control group) born 1948–1953, aged 14–20 years during the policy change. Measurements: Date and diagnosis of the outcome variable of disability pension due to all‐cause, alcohol use disorders and mental disorders were obtained from the Swedish National Social Insurance Agency database from 1971 to 2013. Individual and family level socio‐demographic and health‐related covariates, as well as a regional level covariate, were included. Findings: Compared with the control group, adolescents exposed to the alcohol policy change were at an increased risk of receiving disability pension due to all‐causes [hazard ratio (HR) = 1.09, 95% confidence interval (CI) = 1.07–1.11], alcohol use disorders (HR = 1.17, 95% CI = 1.05–1.30) and mental disorders (HR = 1.19, 95% CI = 1.15–1.23). Conclusion: In Sweden, a natural experiment with a 43‐year follow‐up suggests that exposure to increased alcohol availability during adolescence is associated with an increased risk of receiving a disability pension due to all‐cause, alcohol use disorder and mental disorder diagnoses.